2007
DOI: 10.4067/s0365-28072007000100001
|View full text |Cite
|
Sign up to set email alerts
|

Uso de Marcadores SSR para Identificación de Germoplasma de Papa en el Programa de Mejoramiento de INIA de Chile

Abstract: A B S T R A C TMolecular markers based on Simple Sequence Repeats (SSR) are a very efficient tool for potato (Solanum tuberosum L.) genotype identification and can be very useful for germplasm conservation and management. With the purpose of incorporate this technology into the potato breeding program of the National Institute of Agricultural Research (INIA) Chile, a set of 26 SSR markers was evaluated on a sample of 71 potato genotypes. Each marker was characterized for number and combinations of alleles, sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
(14 reference statements)
1
4
0
3
Order By: Relevance
“…In this study, 64 allelic variants were identified by their approximate sizes, ranging between 110 and 289 bp. The sizes of the alleles found in this study for S. tuberosum were within the range reported by other authors (Moisan-Thiery et al 2005;Mathias et al 2007;Ghislain et al 2009a;Ghislain et al 2009b). A total of 21 alleles were found specific to native varieties, while only five were specific to the commercial cultivars.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In this study, 64 allelic variants were identified by their approximate sizes, ranging between 110 and 289 bp. The sizes of the alleles found in this study for S. tuberosum were within the range reported by other authors (Moisan-Thiery et al 2005;Mathias et al 2007;Ghislain et al 2009a;Ghislain et al 2009b). A total of 21 alleles were found specific to native varieties, while only five were specific to the commercial cultivars.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, efforts have been made to achieve a less subjective description of potato germplasms based on Random Amplified Polymorphic DNA (RAPD) (Sun et al 2003;Orona-Castro et al 2004), microsatellites (Simple Sequence Repeats -SSR) (Ashkenazi et al 2001;Raker and Spooner, 2002;Ghislain et al 2004;Feingold et al 2005;Sukhotu et al 2005;Barandalla et al 2006;Ghislain et al 2006;Ispizúa et al 2007;Mathias et al 2007;Spooner et al 2007, Ghislain et al 2009aGhislain et al 2009b;Lung'aho et al 2011), and Interrupted Simple Sequence Repeats (ISSR) (Milbourne et al 1998;Bornet et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Dada la gran variabilidad de esta especie, los programas de mejoramiento genético necesitan conservar y manejar numerosos genotipos en las colecciones de germoplasma, los cuales, más adelante, pueden ser utilizados como progenitores [5]. La mayoría de estos genotipos son portadores de genes valiosos, relacionados con producción y resistencia a estrés bióticos y abióticos que a través de cruzamientos son transferidos a nuevas variedades mejoradas [6].…”
Section: Introductionunclassified
“…Esto representa un ahorro sustancial de tiempo en la preparación de las muestras y facilita su procesamiento a gran escala. Ventajas que han sido previamente señaladas por otros autores (Mathias et al 2007, De Jesús et al 2005. La coincidencia entre la predicción del sexo por PCR y por morfología floral fue entre un 96 % y un 98 %, independientemente del estado de desarrollo de las plantas de papaya (plantas adultas o plántulas).…”
Section: Evaluación En Campo De Las Plantas Hermafroditas Sexadasunclassified